Conservation of Christo/paik Wrapped Tv (1967): Documentation and Treatment of a Collaborative Artwork. Issue 4 (1st October 2016) - Delidow, Margo; Pace, Jessica; Meier, Eric
Abstract : The conservation of Wrapped TV, a 1967 work by Christo and Nam June Paik, illustrates the practical decisions that arise from the conservation of collaborative works in contemporary art. Wrapped TV consists of Nam June Paik's work, a small CRT inside a poly(methyl methacrylate) sheet box that was wrapped with flexible PVC film and tied with string and twine by Christo. The object has undergone natural deterioration of many components. Separately, extensive damage to the PMMA sheet has distorted the object's shape and rendered it structurally unsound. Three options were available regarding the conservation of the object: leave as-is, work with the artist to recreate the piece, or treat the object. The authors chose to treat Wrapped TV with the aim of providing structural stability with minimal visual impact. This decision was guided by concern for the object's safety, the limited window of time available before the PVC film becomes too brittle to move, and the commitment to preserve the work's 1967 materials and date. The treatment retained original hardware, utilized CAD software to aid in detailed documentation, and used digital machining to fabricate mounts that allowed broken original plastic elements to be stabilized and retained.